LAURA, VERSUS THE DARK LADY, A COMPARATIVE STUDY OF SHAKESPEARE AND PETRARCH’S SONNETS - Mohammadi, Sogand (PEOPLE: International Journal of Social Sciences, 2018)
One was from Italy, and one was from England, and they had a roughly two hundred years’ time span between them. Nevertheless, Both Shakespeare and Petrarch were among the most magnificent sonneteers of Europe and both of them talked about love, and death in their sonnets. Shakespeare urges another, a young man to find love and marry, while Petrarch talks about his own love toward Laura. Shakespeare talks about a dark lady, who hurts the lover (a person other than Shakespeare). Petrarch’s discussions are about his Laura who does not heed his love. Shakespeare talks about death, to frighten and motivate the fair youth to marry, but Petrarch talks about death to show his sadness for the shortness of his time to pursue his lovely Laura. Through a comparative study, this article endeavours to compare the poetical works of two of the most celebrated sonneteers of all times through the aspects of love, hurt and death and tries to show their different worldviews.